Wage inequality in Turkey: Is labor market polarized? - Daş, Zühal Özbay (My University, 2017)
Bu tez, 1994-2015 yılları arasında Türkiye’deki ücret eşitsizliklerindeki gelişmeyi ve 2004-2015 yılları arasında istihdam ve ücret kutuplaşmasının olup olmadığını göstermeyi amaçlamıştır.

This thesis aimed to investigate the evolution of wage inequality from 1994 to 2015 in Turkey and to figure out whether labor market is polarized in terms of employment and wages for the period of 2004-2015.
Keywords: Ekonomik durum; emek talebi; Eonomik eşitsizlikler; Gelir dağılımı; kutuplaşma; labor demand; meslekler; nitelik yönlü teknolojik değişim wage inequality; occupations; polarization; skill biased technological change; Sosyal durum; Türkiye; ücret eşitsizlikleri